REGIONAL DISPARITY ANALYSIS BASED ON REGIONAL FINANCIAL INDEPENDENCE IN CITIES IN EAST JAVA BEFORE COVID-19 PANDEMIC - Muhammad Yasin; Tri Andjarwati; Endah Budiarti; Pramita Studiviany S (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
absorption and concentration of the population in the city center, it is known from the highest population density level in 2014 in Surabaya City, which is 2.874 million people, where Surabaya City is also the city center in East Java Province. How the financial independence of financial management from each region must be different, but why are the regions close to big cities the PAD is not effective and efficient in learning regional needs. On the three criteria for the ratio of financial independence, namely the cities of Kediri, Pasuruan, Probolinggo, Batu, Blitar, and Mojokerto the average is